Adult-onset autosomal dominant spastic paraplegia linked to a GTPase-effector domain mutation of dynamin 2. Issue 1 (December 2015) - Sambuughin, Nyamkhishig; Goldfarb, Lev; Sivtseva, Tatiana; Davydova, Tatiana; Vladimirtsev, Vsevolod; Osakovskiy, Vladimir; Danilova, Al'bina; Nikitina, Raisa; Ylakhova, Anastasia; Diachkovskaya, Margarita; Sundborger, Anna; Renwick, Neil; et al.
Abstract Background Hereditary Spastic Paraplegia (HSP) represents a large group of clinically and genetically heterogeneous disorders linked to over 70 different loci and more than 60 recognized disease-causing genes. A heightened vulnerability to disruption of various cellular processes inherent to the unique function and morphology of corticospinal neurons may account, at least in part, for the genetic heterogeneity. Methods Whole exome sequencing was utilized to identify candidate genetic variants in a four-generation Siberian kindred that includes nine individuals showing clinical features of HSP. Segregation of candidate variants within the family yielded a disease-associated mutation. Functional as well asin-silico structural analyses confirmed the selected candidate variant to be causative. Results Nine known patients had young-adult onset of bilateral slowly progressive lower-limb spasticity, weakness and hyperreflexia progressing over two-to-three decades to wheel-chair dependency. In the advanced stage of the disease, some patients also had distal wasting of lower leg muscles, pes cavus, mildly decreased vibratory sense in the ankles, and urinary urgency along with electrophysiological evidence of a mild distal motor/sensory axonopathy. Molecular analyses uncovered a missense c.2155C > T, p.R719W mutation in the highly conserved GTP-effector domain of dynamin 2. The mutantDNM2 co-segregated with HSP and affected endocytosis when expressed in HeLa cells.In-silico modeling indicated that this HSP-associated dynamin 2 mutation is located in a highly conserved bundle-signaling element of the protein while dynamin 2 mutations associated with other disorders are located in the stalk and PH domains; p.R719W potentially disrupts dynamin 2 assembly. Conclusion This is the first report linking a mutation in dynamin 2 to a HSP phenotype. Dynamin 2 mutations have previously been associated with other phenotypes including two forms of Charcot-Marie-Tooth neuropathy and centronuclear myopathy. These strikingly different pathogenic effects may depend on structural relationships the mutations disrupt. Awareness of this distinct association between HSP and c.2155C > T, p.R719W mutation will facilitate ascertainment of additionalDNM2 HSP families and will direct future research toward better understanding of cell biological processes involved in these partly overlapping clinical syndromes.